Analisis Struktur dan Fungsi pada Satua I Sibakan - Panca Diputra, Dewa Gede; Duana Sutika, I Nyoman; Darsana, I Nyoman (Humanis; Vol 23 No 3 (2019), 2019)
The study examines the satua text entitled I Sibakan with structure and function analysis. This research uses structural theory. The structural theory uses several opinions of literary experts, including: Sukada, Luxemburg, Teeuw, Esten, Nurgiyantoro, Tarigan, Sudjiman, Sukasa, Esten and Kridalaksana. The methods and techniques used in this study are divided into three stages, namely, 1) the stage of providing data using listening methods assisted with translation techniques and recording techniques, 2) the stage of data analysis using qualitative methods assisted by descriptive analysis techniques, 3) the stage of presentation of analysis results use informal methods assisted by using deductive-inductive techniques. After the structural stage is completed, it is continued to function in the use of function theory in Luxemburg's (1984: 94) opinion, stating that the function of a text is the overall traits that together lead to the same goals and their effects. A thing conveyed in a literary work still has to do with the real world that can be understood and accepted by the reader. The results obtained in the study are, the disclosure of the structure that builds each one in the satua I Sibakan text consisting of incidents, plot, character and characterization, setting, theme and mandate. In addition, this study also reveals the aspects of the functions contained in one group I Sibakan . Functions contained in satua I Sibakan include, the functions of religious life, the function of education, social functions, and functions as entertainment.